Challenges experienced by grandparents caring for AIDS orphans in the Western Cape province, South Africa - Furaha Akimanimpaye; Million S. Bimerew; Deliwe R. Petlhu (AOSIS, 2024)
Background: There is limited understanding of the difficulties and experiences faced by grandparents who assume the responsibility of caring for AIDS orphans. Aim: The objective of the study was to investigate and depict the difficulties encountered by grandparents who provide care for AIDS orphans in the Western Cape province of South Africa. Setting: The study was conducted in the City of Cape Town Metropolitan and the Overberg Municipality. Methods: The study used qualitative approach with an exploratory-descriptive design. A purposive sampling technique was utilised to select 25 grandparents. Semi-structured interviews were conducted, audio-recorded, transcribed verbatim, and analysed thematically using ATLAS.ti, version 7. Results: Financial difficulties, a lack of support, HIV and/or AIDS stigma, and dealing with rebellious teenagers were primary challenges affecting the well-being of grandparents. Conclusion: The study found that while financial challenges were significant, other factors such as poor family support contributed to the decline in the well-being of grandparents caring for AIDS orphans. Contribution: The study's results can lead to improved public health programmes that address the identified challenges and health needs of grandparents providing care to AIDS orphans and the orphans under their care.